We'll always have summer / Jenny Han. - Han, Jenny (Penguin Books, 2025)
Isabel has only ever loved two boys, Conrad and Jeremiah Fisher. One broke her heart; the other made her happier than she ever thought she'd be. But each brother is keeping a secret, and this summer Isabel must choose between the Fisher boys, once and for all. Which brother will it be?